2021
DOI: 10.1093/neuros/nyab259
|View full text |Cite|
|
Sign up to set email alerts
|

Surgery for Degenerative Cervical Myelopathy: A Nationwide Registry-Based Observational Study With Patient-Reported Outcomes

Abstract: BACKGROUND Indications and optimal timing for surgical treatment of degenerative cervical myelopathy (DCM) remain unclear, and data from daily clinical practice are warranted. OBJECTIVE To investigate clinical outcomes following decompressive surgery for DCM. METHODS Data were obtained from the Norwegian Registry for Spine Surgery. The primary outcome was cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 49 publications
1
37
2
Order By: Relevance
“…Thus, the risk of neurological deterioration in patients with DCM, which is presumably high as recently demonstrated in a retrospective cohort study ( 24 ), must be considered against surgical complications (e.g., C5 palsy) and unfavorable long-term sequelae (e.g., adjacent level stenosis) ( 25 ). In two large cohort studies in patients with mild DCM ( 15 , 26 ), there was supporting evidence of a significant functional benefit from surgery at 3- to 24-month follow-up. One of these studies reported adverse events at 3-month follow-up in 27.7% of patients ( 26 ).…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the risk of neurological deterioration in patients with DCM, which is presumably high as recently demonstrated in a retrospective cohort study ( 24 ), must be considered against surgical complications (e.g., C5 palsy) and unfavorable long-term sequelae (e.g., adjacent level stenosis) ( 25 ). In two large cohort studies in patients with mild DCM ( 15 , 26 ), there was supporting evidence of a significant functional benefit from surgery at 3- to 24-month follow-up. One of these studies reported adverse events at 3-month follow-up in 27.7% of patients ( 26 ).…”
Section: Discussionmentioning
confidence: 91%
“…All clinics that perform surgery for degenerative cervical disorders in Norway report to the registry [24,26]. More than 80% of all surgeries on degenerative cervical spine in Norway are registered [13]. The study was planned after the data were collected, but before retrieval of data from the registry.…”
Section: Study Populationmentioning
confidence: 99%
“…The total score ranges between 5 and 18. The EMS scores were dichotomized into mild DCM (scores of ≥ 13) and moderate-to-severe (scores between 5 and 12) [13].…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Degenerative spine disorders are a leading cause of lost disability-adjusted life years, work absence worldwide, and place an economic burden on the whole society ranging from individuals, industry and governments 1 , 2 . Degenerative changes in the cervical spine increase with age 3 , and more than 80% of people above the age of 50 have spondylotic changes on magnetic resonance imaging (MRI) 4 .…”
Section: Introductionmentioning
confidence: 99%